Growth Development Paths of Firms—A Study of Smaller Businesses1. (6th January 2014) - Brenner, Thomas; Schimke, Antje
<x xml:space="preserve">Abstract</x> This paper investigates whether firm characteristics that are related to firm growth in the literature are also related to the development path of firms. This means that we test which firm characteristics accompany growth dynamics during a longer period of time, referring to the sequence of growth and decline steps. We examine three variables: firm size, innovation effort, and export share. To this end, we use panel data on 178 German manufacturing firms over the period from 1992 to 2007. We find that the determinants of growth paths are not the same as the determinants of firm growth at one point in time.